Takaful Industrial Research Developments: A Bibliometric Analysis On The Scopus Database - Lukmanul Hakim; Muhklis Sirotul Munir (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2023)
This study aims to describe research development in the takaful industry from 2013 to 2022. This study used bibliometric analysis research methods. The data used is only sourced from research in the takaful industry field indexed by Scopus. There were 261 articles analyzed using Vosviewer software. This research shows that Malaysia is the most significant contributor to research in the takaful industry. Salman is the most prolific writer, with 18 articles. Moreover, the Journal of Islamic Accounting and Business Research became the most popular journal with the most contribution in publishing articles in the takaful industry. Potential future topics are deposit insurance, takaful insurance, and Sharia governance associated with Islamic banking. The contribution of this research can be used as a consideration for discussion topics in research in this field.